2022
DOI: 10.1155/2022/5333171
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Application of Vessel Speed Dynamic Control considering Safety and Environmental Factors

Abstract: The implementation of ship speed control is extremely important in the shipping industry. It is affected by various factors, such as water depth, obstacles, and environmental factors. Traditional speed control methods only consider geographical constraints, which is difficult to achieve the goal of safe navigation and maritime traffic efficiency simultaneously. Accordingly, a two-stage speed dynamic control model is proposed in this study. In the first stage, certain safety navigation factors, including obstac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Te technical means are applicable in new ships; however, they are difcult to realize for existing ships. In terms of the operation mode, there are three main ways to optimize ship energy consumption: route optimization [21,22], speed optimization [23][24][25][26], and trim optimization [27,28]. Route optimization involves fnding the route with the minimum operating cost or minimum energy consumption by combining meteorological, sea conditions, and other information to ensure the shipping safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te technical means are applicable in new ships; however, they are difcult to realize for existing ships. In terms of the operation mode, there are three main ways to optimize ship energy consumption: route optimization [21,22], speed optimization [23][24][25][26], and trim optimization [27,28]. Route optimization involves fnding the route with the minimum operating cost or minimum energy consumption by combining meteorological, sea conditions, and other information to ensure the shipping safety.…”
Section: Introductionmentioning
confidence: 99%
“…Bouman et al [23] summarized and analyzed various energy-saving and emission reduction measures for ships and found that the energysaving efect of ship speed optimization was between 1% and 60%, which is an efective energy-saving measure. Zhou et al [24] established a dynamic speed optimization model using a particle swarm optimization algorithm and obtained an energy-saving efect of 4.38% through a simulation experiment. To reduce the ship's energy consumption, Wang et al [25] and Du et al [26] optimized the ship's speed to minimize energy consumption and achieved good energy-saving results.…”
Section: Introductionmentioning
confidence: 99%